Customer Loyalty and Corporate Image as Determinants of Human Capital Strategy: Evidence from Private Bank Customers in Yogyakarta - Ramsi Ratna; Dolphi Panjitan (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to determine the influence of Customer Loyalty and Corporate Image on Human Capital Strategy in private banks in Yogyakarta. The study was conducted using a quantitative approach through a survey of 145 customer respondents. The results showed that Customer Loyalty did not have a significant effect on Human Capital Strategy, while Corporate Image had a positive but insignificant effect. These findings confirm that human resource management strategies in private banks are more influenced by internal organizational factors than by loyalty or external image. This study contributes to the development of management science, particularly in understanding the relationship between customer perceptions and HR strategy in the banking sector. Furthermore, the research results can provide input for private bank management to pay more attention to the integration of internal and external factors in formulating human capital strategies.